Digital Learning Management and Student Interest: Examining an Edpuzzle-Based Flipped Classroom in Fiqh Instruction - Sari Ulhasanah; Heru Juabdin Sada; Waluyo Eri Wahyudi (Al-Qalam Institue, 2026)
This study aims to examine the effect of an Edpuzzle-based flipped classroom model on students’ interest in learning Fiqh from a digital instructional management perspective. A quantitative approach with an experimental method was employed using a post-test-only control group design. The participants were divided into an experimental group, which received instruction through an Edpuzzle-supported flipped classroom model, and a control group, which was taught using conventional learning methods. Data were collected through a learning interest questionnaire, classroom observations, and documentation. Prior to hypothesis testing, prerequisite analyses were conducted, followed by an independent samples t-test using SPSS to determine the significance of the treatment effect. The findings reveal a statistically significant difference in students’ learning interest between the experimental and control groups, with a significance value lower than 0.05. These results indicate that the integration of flipped classroom strategies with digital media such as Edpuzzle effectively enhances students’ interest in Fiqh learning. The study implies that well-managed digital learning environments and instructional planning play a crucial role in fostering student engagement and motivation. Therefore, the Edpuzzle-based flipped classroom model can be considered an effective instructional management strategy to improve learning interest in religious education contexts.